Gender mainstreaming in local potato seed system in Georgia - Girard, I. (International Potato Center, 2020)
This report presents the study findings associated with the project “Enhancing Rural Livelihoods in Georgia: Introducing Integrated Seed Health Approaches to Local Potato Seed Systems” in Georgia. It also incorporates information from the results of gender training conducted within the framework of the USAID Potato Program in Georgia. The study had three major aims: 1) to understand the gender-related opportunities and constraints impacting the participation of men and women in potato seed systems in Georgia; 2) to test the multistakeholder framework for intervening in root, tuber, and banana (RTB) seed systems as a means to understand the systems themselves and the possibilities of improving gender-related interventions in the potato seed system; and 3) to develop farmers’ leadership skills to facilitate women’s active involvement in project activities. Results of the project assessment identified certain constraints on gender mainstreaming in the potato seed system: a low level of female participation in decision-making processes, women’s limited access to finances that would enable their greater involvement in larger scale potato farming, and a low awareness of potato seed systems and of possible female involvement in associated activities. Significantly, the perception of gender roles and stereotypes differs from region to region in Georgia; this difference is quite pronounced in the target municipalities of Kazbegi, Marneuli, and Akhalkalaki, with the last two having populations of ethnic minorities (Azeri and Armenian, respectively). For example, in Marneuli, although women are actively involved in potato production, they are not considered farmers but mainly as assistants to farmers, who are men. This type of diversity (or lack thereof) results in a different understanding of gender mainstreaming in the potato seed system as well. Based on the training results obtained in three target regions—Akhalkalaki, Akhaltsikhe, and Marneuli—it is evident that women are keen on learning new technologies and on acquiring updated agricultural information, including on potato production. It is also clear that women spend as much time as men do on farming activities such as potato production, particularly in weeding and harvesting. However, women are heavily burdened with domestic work, and they are not major decision-makers with regard to potato variety selection, agricultural investments, and product sales, nor with the inclusion of participants in any training provided. Involving women in project activities will lead to greater efficiency in the potato production environment, as women’s increased knowledge will certainly contribute to an improved production process, and their new ideas will help to improve existing production systems, through which women could also gain confidence and power. As a general recommendation, it is extremely important to develop equitable seed systems that take into consideration, among other factors, social context and the cultural aspects of local communities. Thus, understanding male and female farmers’ knowledge may promote the development of seed systems that are sustainable and responsive to farmers’ needs and capacities.